Use of Implementation Science Concepts in the Study of Misinformation: A Scoping Review - Bang, Carla; Carroll, Kelly; Mistry, Niyati; Presseau, Justin; Hudek, Natasha; Yanikomeroglu, Sezgi; Brehaut, Jamie C. (Health education & behavior, 2025)
Misinformation hinders the impact of public health initiatives. Efforts to counter misinformation likely do not consider the full range of factors known to affect how individuals make decisions and act on them. Implementation science tools and concepts can facilitate the development of more effective interventions against health misinformation by leveraging advances in behavior specification, uptake of evidence, and theory-guided development and evaluation of complex interventions. We conducted a scoping review of misinformation literature reviews to document whether and how important concepts from implementation science have already informed the study of misinformation. Of 90 included reviews, the most frequently identified implementation science concepts were consideration of mechanisms driving misinformation (78%) and ways to intervene on, reduce, avoid, or circumvent it (71%). Other implementation science concepts were discussed much less frequently, such as tailoring strategies to the relevant context (9%) or public involvement in intervention development (9%). Less than half of reviews (47%) were guided by any theory, model, or framework. Among the 26 reviews that cited existing theories, most used theory narratively (62%) or only mentioned/cited the theory (19%), rather than using theory explicitly to interpret results (15%) or to inform data extraction (12%). Despite considerable research and many summaries of how to intervene against health misinformation, there has been relatively little consideration of many important advances in the science of health care implementation. This review identifies key areas from implementation science that might be useful to support future research into designing effective misinformation interventions.